Radiotherapy in the Adjuvant and Advanced Setting of CSCC - Paolo Muto (Mattioli1885, 2021)
Introduction: The use of radiotherapy for cutaneous squamous cell carcinoma (CSCC) has solid historical roots. It is used with patients who are not suitable for surgery, patients with high-risk histological features in the adjuvant setting, and in palliative care.